2018
DOI: 10.1002/ese3.182
|View full text |Cite
|
Sign up to set email alerts
|

AlGaAs/Si dual‐junction tandem solar cells by epitaxial lift‐off and print‐transfer‐assisted direct bonding

Abstract: A novel method is developed to realize a III-V/Si dual-junction photovoltaic cell by combining epitaxial lift-off (ELO) and print-transfer-assisted bonding methods. The adoption of ELO enables III-V wafers to be recycled and reused, which can further lower the cost of III-V/Si photovoltaic panels. For demonstration, high crystal quality, micrometer-thick, GaAs/AlGaAs/GaAs films are lifted off, transferred, and directly bonded onto Si wafer without the use of any adhesive or bonding agents. The bonding interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…[ 1 ] Importantly, these NMs are compatible with the traditional semiconductor manufacture approach for fabricating various heterogeneously integrated and flexible electronic devices, [ 2–4 ] including the seamless integration of semiconductor NMs with the low‐cost, complementary‐metal‐oxide‐semiconductor‐compatible silicon (Si) substrates. Until now, several applications of transferrable monocrystalline NMs based on Si, [ 4–20 ] germanium (Ge), [ 4,21 ] gallium arsenide (GaAs)/aluminum gallium arsenide (AlGaAs), [ 4,22–26 ] gallium nitride (GaN)/aluminum gallium nitride (AlGaN), [ 27–30 ] silicon carbide (SiC), [ 31 ] gallium oxide (Ga 2 O 3 ), [ 32–35 ] etc. have been reported during the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Importantly, these NMs are compatible with the traditional semiconductor manufacture approach for fabricating various heterogeneously integrated and flexible electronic devices, [ 2–4 ] including the seamless integration of semiconductor NMs with the low‐cost, complementary‐metal‐oxide‐semiconductor‐compatible silicon (Si) substrates. Until now, several applications of transferrable monocrystalline NMs based on Si, [ 4–20 ] germanium (Ge), [ 4,21 ] gallium arsenide (GaAs)/aluminum gallium arsenide (AlGaAs), [ 4,22–26 ] gallium nitride (GaN)/aluminum gallium nitride (AlGaN), [ 27–30 ] silicon carbide (SiC), [ 31 ] gallium oxide (Ga 2 O 3 ), [ 32–35 ] etc. have been reported during the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Because freestanding semiconductors can be precisely placed using a micro-transfer printing method, stacked freestanding semiconductors with various optical bandgaps can be used to demonstrate multicolor photosensors or multijunction solar cells which are difficult to realize with traditional optoelectronic materials. Rigid versions of these photosensors and photovoltaics were recently realized by Menon et al and Chang et al [119,120] which showed that this concept can be applied to flexible optoelectronics, taking advantage of transferable/stackable freestanding semiconductors.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The thinness of NM materials makes them ideal for applications that exploit features other than capacities for flexure as well. Notable examples are illustrated in recently reported designs for applications in photovoltaics. ,,,, For materials with high optical absorptivity, such as is the case for direct band gap III-V semiconductors, thin devices can reduce costs and improve commercial viability without compromising power conversion efficiencies. There has been extensive work directed toward improving light management in these thin solar cells, with promising potential for future developments in technology. ,,, Such structures can also be shaped to adopt curvilinear forms to improve capacities for light management and extend the capabilities of light-concentrating photovoltaics (CPV). ,, …”
Section: Electronic and Optoelectronic Nanomembrane Device Applicationsmentioning
confidence: 99%
“…One interesting application of epitaxial III-V NMs is found in their integration onto Si devices. ,,,,, The heterogeneous integration of compound semiconductors can benefit Si-based lasers, as their direct bandgap provides a route to higher achievable efficiencies. For example, InGaAsP was utilized as the active region in a photonic crystal bandedge laser (Figure d), where an InGaAsP multiquantum well NM was transfer printed onto a Si photonic crystal cavity .…”
Section: Electronic and Optoelectronic Nanomembrane Device Applicationsmentioning
confidence: 99%